The relationship between rheumatoid arthritis (RA) and psychiatric disorder - Monika Kaźmierczak; Oskar Tudaj; Wiktoria Kalas; Krzysztof Sajewicz; Julia Dulęba; Julia Kalisiak; Mikołaj Musiał; Maciej Hobot; Aleksandra Mazur; Filip Kin (Quality in Sport, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that has a destructive effect on the joints, but also leads to many systemic complications, including mental disorders. This review will present the co-occurrence of mood disorders, such as depression, anxiety and cognitive disorders, in patients with RA and analyze the potential pathophysiological mechanisms. The impact of chronic inflammation and proinflammatory cytokines (IL-6, IL-1β, TNF-α) on the central nervous system and the hypothalamic-pituitary-adrenal axis (HPA) will be discussed. When rheumatoid arthritis (RA) is accompanied by mental health disorders, treatment methods used for RA may be less effective. This can make the condition harder to manage, increasing pain and reducing the quality of life. Additionally, the paper will present the impact of pain, fatigue and reduced physical fitness on the deterioration of the mental health of patients. In addition to the pharmacological treatment used for RA, which is also not neutral to patient’s health, additional therapeutic options such as psychological interventions will be discussed. Considering both somatic and psychological aspects, an interdisciplinary approach to the treatment of patients with RA is very important.